Governo eletrônico na gestão ambiental do estado da bahia: avaliação de desempenho do portal seia, na perspectiva dos usuários e gestores - SILVA, Jefferson Lima Da (2014)
The electronic government applied to Brazilian environmental governance has intensified over the past few years as alternative technology to track and manage human actions on the environment, to minimize the difficulties and the inexorable slowness of the state in the management of natural resources, and ensure greater involvement, commitment and participation of society with environmental causes. This research aims to analyze the stage of maturity of e-government, the overall quality perceived by users and the usability of the channel, and organizational factors affecting the provision of services in the Electronic Portal of the State Environmental Information System and Water Resources of the State of Bahia (SEIA). And for that, qualitative and quantitative research methods to guarantee the mapping and understanding the variables correlated with user satisfaction and managers of environmental services provided by Portal SEIA were adopted, seeking to understand what features and/or information that best explain the satisfaction of users of the channel, or even posing as limiters and/or facilitating the provision of e-government public services in environmental ambience of Bahia.